2017
DOI: 10.1159/000477090
|View full text |Cite
|
Sign up to set email alerts
|

Homöopathisch-phytotherapeutische Behandlung des Reizdarmsyndroms mit Magen-Darm-Entoxin N®: Eine Anwendungsbeobachtung

Abstract: Hintergrund: In dieser Anwendungsbeobachtung wird zum ersten Mal die Behandlung des Reizdarmsyndroms (RDS) mit einem homöopathisch-phytotherapeutischen Komplexpräparat beschrieben. Methodik: Ziel der 6-wöchigen Therapie mit dem Magen-Darm-Entoxin N® war die Reduzierung der RDS-Symptomatik sowie die Verbesserung der Lebensqualität. Zielkriterien waren die Veränderungen in der Irritable Bowel Syndrome - Severity Scoring System (IBS-SSS) und der Irritable Bowel Syndrome - Quality-of-Life Scale (IBS-QoL). Die Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The effectiveness of MDE, a well-established (1930ies) and effective remedy in the treatment of IBS, was already proved in an observational study [2], but up to now, potential mechanisms of action have still been unknown. Inflammation is a common mechanism of many FGIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of MDE, a well-established (1930ies) and effective remedy in the treatment of IBS, was already proved in an observational study [2], but up to now, potential mechanisms of action have still been unknown. Inflammation is a common mechanism of many FGIDs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, it was presented as a treatment for irritable bowel syndrome (IBS) in an observational study and was found to be a save and reasonable therapeutic option. The target criterion was the change of the IBS Symptom Severity Scale and the IBS Quality of Life Scale [2].…”
Section: Introductionmentioning
confidence: 99%